Intra‐ and interobserver reproducibility of Bruch's membrane opening minimum rim width measurements with spectral domain optical coherence tomography. Issue 7 (26th June 2017) - Reis, Alexandre S. C.; Zangalli, Camila e S.; Abe, Ricardo Y.; Silva, André L.; Vianna, Jayme R.; Vasconcellos, José Paulo C.; Costa, Vital P.
Abstract: Purpose: To investigate the reproducibility of Bruch's membrane opening minimum rim width (BMO‐MRW) and retinal nerve fibre layer thickness (RNFLT) measurements using spectral domain optical coherence tomography (SD‐OCT). Additionally, to investigate the reproducibility of BMO area measurements and fovea to BMO centre (FoBMO) angle. Methods: Participants were healthy subjects ( n  = 30) and patients with glaucoma ( n  = 26). One eye of each participant was scanned to obtain optic nerve head (24 radial B‐scans) and peripapillary (one circular B‐scan) images by three independent examiners. Additionally, one examiner imaged each participant three times on the same day. Intra‐ and interobserver reproducibilities were estimated by within‐subject standard deviation (SW) and coefficient of variation (COV). Spearman's rank correlation coefficient was used to test the correlation between the magnitude of the parameter and its standard deviation. Results: The global BMO‐MRW COVs (%) in healthy/glaucoma subjects were 0.87/1.34 and 1.28/3.13 for intra‐ and interobserver analyses, respectively, and the corresponding global RNFLT figures were 1.50/2.10 and 2.04/2.87. Global mean BMO‐MRW and RNFLT showed no correlation with their respective standard deviations. The reproducibilities of BMO area and FoBMO angle were excellent and similar between the groups. Conclusion: The reproducibilities of BMO‐MRW, BMO area measurements and FoBMO angle were excellent in both healthy subjects and patients with glaucoma. Bruch's membrane opening minimum rim width (BMO‐MRW) reproducibility is comparable to that of RNFLT measurements.